Metastatic mesenteric dedifferentiated leiomyosarcoma: a case report and a review of literature. Issue 1 (December 2016) - Varghese, Mercy; Bruland, Oyvind; Wiedswang, Anne; Lobmaier, Ingvild; Røsok, Bård; Benjamin, Robert; Hall, Kirsten
Abstract Background Abdominal leiomyosarcoma arising from the mesentery is a rare malignancy. It is an aggressive entity with an overall 5 year survival rate between 20 and 30 %. Surgical resection is the cornerstone of primary treatment and may be curative for localized disease. However, patients often develop intra-abdominal relapse and/or metastatic disease. If surgical resection is not feasible, palliative chemotherapy is the treatment of choice. However, there are no clear guidelines regarding chemotherapy; neither in the adjuvant nor advanced setting. Case presentation We present a 40 year-old woman, with a mesenteric leiomyosarcoma, who underwent radical tumor resection and did not receive adjuvant oncological therapy. Three months postoperatively, she developed metastatic disease to the lungs and liver. After multidisciplinary assessment she received an unconventional histological-subtype-tailored chemotherapy comprising 3–4 regimens. Initially, there was a decrease both in number and size of metastases. Ultimately, an almost complete radiological response was seen. Subsequent surgical resection and radiofrequency ablation of residual metastatic foci in the liver and lung brought her into complete clinical remission. She is presently tumor free, 36 months following diagnosis of metastatic disease. Conclusions To our knowledge, this is the first report of a patient with metastatic mesenteric leiomyosarcoma who is in complete clinical and radiological long-term remission following very aggressive multimodal treatment; including intense poly-drug chemotherapy and without any demonstrable long-term side effects. Given the rarity of mesenteric leiomyosarcoma and lack of guidelines regarding oncological therapy, we suggest that multimodal therapy including aggressive chemotherapy, guided by a multidisciplinary team, is essential to achieve an optimal outcome.